Perceived technostress while learning a new mobile technology: Do individual differences and the way technology is presented matter? - Jurek, Paweł; Olech, Michał; Brycz, Hanna (Human Technology, 2021)
A growing body of research demonstrates that using technology can – despite the obvious benefits – be associated with stress. The aim of this study was to explore how perceived technostress while learning a new pro-healthy technology may be grounded in dispositional anxiety, attitudes towards ICT (Information and Communication Technologies), and the way technology is presented. Verifying the hypotheses, a study was conducted with the participation of N = 1,037 individuals, in which the ’technology presentation’ was manipulated and selected individual differences were measured. As expected, it was found that presenting the new technology in the form of a popular science article was associated with the perception of this technology as more threatening and overloading compared to the situation in which the technology was presented in the form of a marketing leaflet with an unequivocally positive message. Moreover, it was shown that people characterized by higher dispositional anxiety perceived the new technology as more stressful in terms of examined categories of techno-stressors. Support was also found for the hypothesis that attitudes towards ICT corelate to selected dimensions of perceived technostress in regard to newly learned technology. However, the small extents of the effect obtained in the study indicated the need to continue searching for substantial factors that would predict technostress at the early stages of learning a new technology.